Microbiological assessment of spaghetti from selected franchised food establishment in Iloilo City - Cordero, Claudette Mae Sanchez (2008.)
The spaghetti purchased from a franchised food establishment was under assessment for safety quality.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Spaghetti